2019
DOI: 10.1093/jas/skz122.433
|View full text |Cite
|
Sign up to set email alerts
|

PSI-9 Validation of environmental swabbing to detect Senecavirus A in feed

Abstract: Senecavirus A (SVA) is an emerging virus impacting the U.S. swine herd. Environmental swabbing can help better detect the probability of feed contamination than product testing, but the detection of SVA by swabs has not yet been validated. Therefore, the objective of this experiment was to validate standardized swabbing techniques for detection of SVA. A secondary objective was to determine if a freeze/thaw cycle impacted detectable RNA. This experiment was a 3×4×2 factorial, with 3 forms (inoculum, feed, or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The challenge in loss of sensitivity is not confined to PEDV. We recently observed a similar CT sensitivity loss between liquid inoculum and dry feed with Senecavirus A (SVA) (Sardella et al, 2019). Furthermore, Dee et al (2018) reported a loss in sensitivity between stock virus and various ingredients or complete feed for SVA, BVDV (surrogate for CSFV), PRRSV, and ASFV.…”
Section: Future Directions For Swine Feed Safetymentioning
confidence: 78%
See 1 more Smart Citation
“…The challenge in loss of sensitivity is not confined to PEDV. We recently observed a similar CT sensitivity loss between liquid inoculum and dry feed with Senecavirus A (SVA) (Sardella et al, 2019). Furthermore, Dee et al (2018) reported a loss in sensitivity between stock virus and various ingredients or complete feed for SVA, BVDV (surrogate for CSFV), PRRSV, and ASFV.…”
Section: Future Directions For Swine Feed Safetymentioning
confidence: 78%
“…The challenge in loss of sensitivity is not confined to PEDV. We recently observed a similar CT sensitivity loss between liquid inoculum and dry feed with Senecavirus A (SVA) (Sardella et al ., 2019). Furthermore, Dee et al .…”
Section: Future Directions For Swine Feed Safetymentioning
confidence: 99%
“…A decision tree has been developed by the Swine Health Information Center to help facilities identify high-risk ingredients (Swine Health Information Center, 2018). (Sardella et al, 2019;. This type of environmental monitoring can establish baseline Enterobacteriaceae levels in facilities, and identify poor hygiene areas that are likely to be risk points for pathogen entry.…”
Section: Prevention Of Entrymentioning
confidence: 99%